Effects of cover crop on selected abiotic and biotic soil health indicators - Samuel I. Haruna (Environmental Challenges, 2024)
Current cropping systems, like cover cropping, aim to improve soil health and crop productivity, with the former a more sustainable route to the latter. This can be done by evaluating the influence of cover crops (CCs) on soil health indicators, both abiotic and biotic, as is the objective of this study. Several CCs (crimson clover [Trifolium incarnatum L.], oats [Avena sativa], hairy vetch [Vicia villosa Roth.], winter wheat [Triticum aestivum L.], winter peas [Lathyrus hirsutus L.], flax [Linum usitassimum L.], triticale [Triticale hexaploide Lart.], cereal rye [Secale cereale], and barley [Hordeum vulgare L.]) were used across two research sites, set up using a completely randomized design with two levels of CCs (CC vs no cover crop [NC]) and three replicates during 2023. Soil samples were collected at 0–10, 10–20, and 20–30 cm depths and analyzed for soil physico-chemical properties and microbial biomass and composition. Results showed significantly lower bulk density values, greater water content (at 0 kPa soil water matric potential), greater volume-specific heat capacity (at 0 and -33 kPa soil water matric potential), greater total nitrogen, and numerically greater soil organic carbon under CC compared with NC management. This led to numerically greater microbial biomass and community composition (e.g., arbuscular mycorrhizal fungi, gram-negative and gram-positive bacteria, eukaryotes, and fungi), and slightly lower microbial stress indicators (genotypic and chemical structure categorizations) under CC compared with NC management. However, the lack of significant differences between treatments suggests that three years is insufficient to detect improvements in measured soil health indicators. Further, the significant differences in measured soil health indicators between study sites suggests an influence of soil texture and order, and this warrants further investigations.